(3JLQjO GdCUhd aj CMGOjK GdQShds - (3TQa GdOjf CHh GdbGSe gHg Gddg Hf YHO GdQMje GdHGQRis; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3CMeO Hf YeQ Hf CHj HcQ GdCSOi s)
(3ChdgG (B:s
,(3HYO , abO hbaJ Ydi cJH YOI eeG Ohfg GdYdeGA ai CMGOjK GdQShd Udi Gddg Ydjg hSde (B" (3hSeYhg hQhGg GdKbGI Yf Sda GdUMGHI QVi Gddg Yfge hLeYhg s
(3BNQgG (B:s
(3BNQg CKfGA cJGH GdUaGI bhdg (B: (3hQCjJ QShd Gddg Udi Gddg Ydjg hSde jVY GdgGeI Ydi CPfg hGdJi jdjgG Ydi Yjfg Je GdLRA GdChd ef cJGH JLQjO GdCUhd GdeSJNQL ef LGeY GdCUhd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3GdMOjK h GdeUWdMs